2020
DOI: 10.1097/brs.0000000000003375
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Distal Fusion Level for Lenke 5 Curve

Abstract: Study Design. A retrospective analysis. Objective. To evaluate whether the rotation of the presumed lower instrumented vertebra (LIV) on baseline convex side-bending (SB) radiographs leads to distal adding-on in Lenke 5C adolescent idiopathic scoliosis (AIS) patients. Summary of Background Data. In Lenke 1A patients, derotation of the presumed LIV on baseline bending films is important owing to the associati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…The former group satisfied two of the three criteria for transient L4 fixation in this study. Similarly, Shu et al 11 reported worse results with a LIV tilting angle of 11.0 ± 3.5° in patients with adding-on phenomenon than the group without adding-on phenomenon with LIV (L3) in Lenke Type 5C scoliosis. In this study, the final LIV (L3) tilting angle was 4.7 ± 2.2°.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…The former group satisfied two of the three criteria for transient L4 fixation in this study. Similarly, Shu et al 11 reported worse results with a LIV tilting angle of 11.0 ± 3.5° in patients with adding-on phenomenon than the group without adding-on phenomenon with LIV (L3) in Lenke Type 5C scoliosis. In this study, the final LIV (L3) tilting angle was 4.7 ± 2.2°.…”
Section: Discussionmentioning
confidence: 83%
“…Despite advances in scoliosis surgeries, there is still a major controversy regarding the distal fusion level for idiopathic scoliosis surgery 5,[7][8][9][10][11][12][13][14] . A 40-year follow-up study by Lander et al 12 indicated that there was a higher risk of additional surgery and poorer functional outcome after L4 or below L4 fixation in idiopathic scoliosis surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, lower end vertebra is not far from CSVL. Shu found that horizontalization of the LIV and minimizing LIV translation during correction could reduce the risk of distal adding-on [ 18 ]. In a meta-analysis, Yang evaluated the incidence, characteristics, and risk factors for "adding-on", and demonstrated that lowest instrumented vertebra (LIV)-center Sacral Vertical Line (CSVL) and deviation of LIV + 1 were found to be significantly associated with "adding-on" [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Second, lower end vertebra should be well derotated. Shu also demonstrated that derotation of the presumed LIV on SB films may hint less risk of distal adding-on in Lenke 5c patients [ 18 ]. In another word, well derotation could reduce the incidence of adding-on.…”
Section: Discussionmentioning
confidence: 99%